Comparative experience of social support for the population in the context of the EAEU during the global pandemic - N. S. Sabyr; N. A. Abilkaiyr (Экономика: стратегия и практика, 2021)
This article provides a comparative analysis of the social policies of the EAEU member states during the 2020 corona virus pandemic. The key directions of social policy are considered, a review of the effectiveness of social measures to protect the population is carried out. As part of the fight against the coronavirus pandemic, the governments of the EAEU member states have taken a set of measures to overcome the crisis and provide social support to the population. The authors of the article carried out a comparative analysis of the effectiveness of the social policy aimed at supporting the population during a pandemic. A comparative analysis of the social policy pursued by the EAEU member countries during the pandemic showed the presence of a single set of social support measures. These are, first of all, payments for unemployment and disability, payments to families with children, subsidies for housing and communal payments, and preferential loans. The country specificity is characterized by the amount of benefits provided and the criteria for selecting the objects of granting benefits. The need to provide support measures for the population for a long time, due to the general situation with coronavirus in the world, puts significant pressure on the state budgets of countries and can lead to an increase in public debt and aggravation of general economic problems.